دور برامج تدريب وتأهيل المعلمين في أكاديمية الملكة رانيا العبدالله في تنمية المسؤولية المهنية للمعلم والاتجاه نحو المهنة - الصوالحة، على سليمان; العويمر، يسرى راشد; الحمران، محمد خالد محمد (الجامعة الإسلامية بغزة - شئون البحث العلمي والدراسات العليا, 2021)
هدفت هذه الدراسة إلى معرفة دور برامج تدريب وتأهيل المعلمين في أكاديمية الملكة رانيا العبد الله في تنمية المسؤولية المهنية للمعلم والاتجاه نحو المهنة. اتبعت الدراسة المنهج الوصفي المسحي من خلال إعداد استبانتين: الأولى مكونة من (20) فقرة، هدفت لقياس دور برامج تدريب وتأهيل المعلمين في أكاديمية الملكة رانيا العبد الله في تنمية المسؤولية المهنية للمعلم، والثانية مقياس للاتجاهات نحو المهنة وتكون من (17) فقرة، وتم توزيع الأداتين على عينة الدراسة البالغة (213) معلمة تم اختيارهن عشوائياً. وقد أظهرت النتائج أن تقديرات المعلمين لدور برامج تدريب وتأهيل المعلمين في أكاديمية الملكة رانيا العبد الله في تنمية المسؤولية المهنية للمعلم والاتجاه نحو المهنة كانت مرتفعة. وكما أظهرت النتائج عدم وجود فروقات ذات دلالة إحصائية لدور برامج تدريب وتأهيل المعلمين في أكاديمية الملكة رانيا العبد الله بالنسبة لتنمية المسؤولية المهنية للمعلم تعزى لمتغير المؤهل العلمي. وقدمت الدراسة مجموعة من التوصيات.
The aim of this study is to assess the Role of teacher's training programs at Queen Rania Al Abdullah Academy in developing the professional responsibility of the teacher and the attitudes towards career. The study followed the descriptive method by developing two questionnaires: the first one consists of (20) paragraphs, aimed at measuring the Role of training programs and rehabilitation of teachers at the Queen Rania Al Abdullah Academy in developing the professional responsibility of the teacher while the second one consists of (17) paragraphs aimed at measuring the trends towards career. The study sample was (213) female teachers that were randomly selected. The results showed that the teachers' assessment of the Role of teacher training programs in the Queen Rania Al Abdullah Academy in developing the professional responsibility of the teacher and attitudes towards career was high. The results also showed that there were no significant differences in teachers' estimations of the Role of teacher training programs in Queen Rania Al Abdullah University in developing the professional responsibility of the teacher due to scientific qualification. The study presented a set of recommendations.
Keywords: المؤسسات الأكاديمية -- البرامج التدريبية -- التأهيل المهني -- المهارات التدريسية -- الكفايات التعليمية